2021
DOI: 10.1097/rlu.0000000000003869
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Proton Magnetic Resonance Spectroscopy and 18F-Fluorocholine PET to Differentiate Benign From Malignant Breast Lesions

Abstract: Purpose The aim of this study was to evaluate the diagnostic performance of the proton magnetic resonance spectroscopy (MRS) and 18F-fluorocholine (FCH) PET for suspicious breast findings on conventional imaging (mammography and breast ultrasound). Methods From September 2012 to December 2015, 37 women with 39 breast lesions on conventional imaging were enrolled and underwent proton MRS and FCH PET. The MRS parameters of choline signal-to-noise ratio (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It was found out that MRS results in higher accuracy, sensitivity and specificity regarding detection of malignant breast lesions. A study conducted by Wu L-A et al reported sensitivity and specificity of MRS in detecting breast malignancy to be 91% and 93% respectively (Wu et al, 2021). In a metaanalysis, data from 19 studies was pooled (Gu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was found out that MRS results in higher accuracy, sensitivity and specificity regarding detection of malignant breast lesions. A study conducted by Wu L-A et al reported sensitivity and specificity of MRS in detecting breast malignancy to be 91% and 93% respectively (Wu et al, 2021). In a metaanalysis, data from 19 studies was pooled (Gu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“… 40 In a recent study by Wu et al comparing MRS and 18 F‐choline uptake in 39 benign and malignant breast lesions, a moderate comparison was found between MRS and PET parameters. 41 Furthermore, in their study, the PET‐based standard uptake value (SUV) obtained with the patient in the supine position was shown to be the best performing parameter for breast cancer diagnosis, with an area under the curve (AUC), sensitivity, and specificity were 0.918, 89.5%, and 87.5%, respectively, using a cut‐off of 2.5. Clinical investigations for the feasibility and usefulness of 18 F‐choline PET/MRI of the breast are currently ongoing.…”
Section: Pet Tracersmentioning
confidence: 99%
“…In regards to 18 F‐choline, one of the first evidence of its applicability in breast cancer assessment was the incidental invasive breast cancer finding in a male patient which showed high 18 F‐choline uptake during a prostate examination 40 . In a recent study by Wu et al comparing MRS and 18 F‐choline uptake in 39 benign and malignant breast lesions, a moderate comparison was found between MRS and PET parameters 41 . Furthermore, in their study, the PET‐based standard uptake value (SUV) obtained with the patient in the supine position was shown to be the best performing parameter for breast cancer diagnosis, with an area under the curve (AUC), sensitivity, and specificity were 0.918, 89.5%, and 87.5%, respectively, using a cut‐off of 2.5.…”
Section: Pet Tracersmentioning
confidence: 99%
“…The role of 18F-FEC in breast lesions has been addressed by only few studies, which presented several limitations and included only malignant lesions [ 7 , 11 , 12 ]. A single work on 39 breast lesions showed the potential of 18F-FEC to differentiate benign from malignant breast lesions [ 13 ]. The full potential of 18F-FEC as an imaging biomarker for diagnostic purposes and prediction of breast cancer aggressiveness remains elusive.…”
Section: Introductionmentioning
confidence: 99%